Interplay between structure and properties in acid-base blend PBI-based membranes for HT-PEM fuel cells - Giffin, Guinevere A.; Galbiati, Samuele; Walter, Mario; Aniol, Karin; Ellwein, Corina; Kerres, Jochen; Zeis, Roswitha (Journal of Membrane Science, 2017)
This work is the follow-up to a previous study in which the same authors extensively documented the behaviour of acid-base polymer blend membranes doped with phosphoric acid during high temperature (160 °C) fuel cell operation. The present study examines the same acid-base blend PBI-based materials to obtain a deeper understanding of the relationship between the chemical structure and the membrane properties, particularly in the presence of phosphoric acid. At high doping temperatures, i.e. 120–130 °C, the ionic crosslinks of the acid-base blends limit both the acid doping level and the swelling as compared to purely basic polymers. However, the relationship between ionic crosslinks, acid doping level and swelling is complex and affected not only by the possible number of cross-links, but also by the hydrophilicity of the basic polymer, the geometry or distribution (or both) of the crosslinks and the structure of the acidic polymer. Spectroscopy shows that an acid-base reaction occurs between the PBI basic sites and PA, resulting in a protonated benzimidazolium and H2PO4 -, but there is also spectral evidence of free acid in the membrane when it is doped at high temperature. Within the family of F6PBI (poly(2-(4-(1,1,1,3,3,3-hexafluoro-2-phenylpropan-2-yl)phenyl)-3H,3′H-5,5′-bibenzo[d]imidazole)) materials, the conductivity increases with the acid doping level. PBIOO (poly(6-((1H-benzo[d]imidazol-6-yl)oxy)-2-(4-phenoxyphenyl)-1H-benzo[d]imidazole)) blends exhibit higher proton conductivity than F6PBI blends and commercial m-PBI. However, there is no distinct trend for the conductivity within the PBIOO blends. The thermal stability of the materials is reduced when PA is present in the membranes. Acid-base blends preserve the good mechanical properties in terms of tensile strength and modulus after doping at 120 °C in concentrated PA, which is not possible for commercial m-PBI. These materials could achieve high mechanical integrity and longer endurance in HT-PEMFC long term operation (as previously reported), while maintaining good proton conductivity.
CRIS-Team Scopus Importer:2023-08-01
Keywords: Acid-base blend membranes; Fuel cell; HT-PEM fuel cell; Phosphoric acid doping; Polybenzimidazole